Retinoid X receptor γ interacts with peroxisome proliferator-activated receptor-γ to promote browning during adipose tissue differentiation - Defei Chen; Saed Woraikat; Xiong Guo; Fuyu Yang; Chenglin Tang; Fan He; Kun Qian (Adipocyte)
Obesity and type 2 diabetes mellitus are global public health challenges. Activating thermogenic adipose tissues, such as brown adipose tissue and beige adipose tissue, could be a promising strategy to combat obesity and consequently obesity-related diabetes. Both peroxisome proliferator-activated receptor-γ (PPARγ) and retinoid X receptor γ (RXRγ) play significant roles in the regulation of adipogenic differentiation. However, the underlying mechanisms and interactions between these receptors during adipogenic differentiation remain unclear. In this study, we conducted a comprehensive analysis of a transcriptome sequencing dataset sourced from the GEO database, encompassing samples of white and brown adipose tissues from 15 healthy individuals. Our findings reveal that RXRγ expression is significantly elevated in brown adipose tissue relative to white adipose tissue (p = 0.041). Furthermore, co-immunoprecipitation assays validated that RXRγ can be co-precipitated with PPARγ. Subsequent luciferase assays demonstrated that the interaction between RXRγ and PPARγ significantly enhances the transcriptional activity of uncoupling protein 1 (UCP1) compared to the overexpression of PPARγ alone (3.4-fold vs. 1.5-fold, p < 0.001). Notably, in human preadipocytes, the co-overexpression of RXRγ with PPARγ resulted in a significant increase in UCP1 transcriptional activity compared to the overexpression of PPARγ alone (3.4-fold vs. 2.0-fold, p < 0.05). In summary, our findings suggest that RXRγ serves as a novel cofactor for PPARγ, promoting the browning of adipose tissue through the upregulation of UCP1 transcription.